2023
DOI: 10.1002/adma.202205409
|View full text |Cite
|
Sign up to set email alerts
|

Manganese‐Based Tumor Immunotherapy

Abstract: As an essential micronutrient, manganese (Mn) participates in various physiological processes and plays important roles in host immune system, hematopoiesis, endocrine function, and oxidative stress regulation. Mn‐based nanoparticles are considered to be biocompatible and show versatile applications in nanomedicine, in particular utilized in tumor immunotherapy in the following ways: 1) acting as a biocompatible nanocarrier to deliver immunotherapeutic agents for tumor immunotherapy; 2) serving as an adjuvant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 125 publications
(180 reference statements)
0
39
0
Order By: Relevance
“…Over the past few decades, studies have shown that metal ions such as Zn 2+ , Ca 2+ , and Mn 2+ etc. play important roles in the activation of innate or adaptive immunity. , Diverse small molecules including metal ions have been developed as immunostimulatory adjuvants to augment antigen immunogenicity. In particular, Mn 2+ has been demonstrated to activate the cyclic GMP-AMP synthase (cGAS) and stimulator interferon gene (STING) pathway and is able to synergize with immune checkpoint inhibitors for cancer immunotherapy. , However, unfavorable pharmacokinetics and possible neurotoxicity of Mn 2+ limited its wide applications in cancer immunotherapy . To improve the efficacy, various nanoparticle-based formulations have been developed to improve the immune activation effect of Mn 2+ . The formulation of Mn 2+ with antigens into a subunit cancer nanovaccine may be advantageous for spatiotemporal codelivery of the subunit antigens and Mn 2+ to the cytoplasm, where they may achieve orchestrated immune responses in the subcellular compartment.…”
mentioning
confidence: 99%
“…Over the past few decades, studies have shown that metal ions such as Zn 2+ , Ca 2+ , and Mn 2+ etc. play important roles in the activation of innate or adaptive immunity. , Diverse small molecules including metal ions have been developed as immunostimulatory adjuvants to augment antigen immunogenicity. In particular, Mn 2+ has been demonstrated to activate the cyclic GMP-AMP synthase (cGAS) and stimulator interferon gene (STING) pathway and is able to synergize with immune checkpoint inhibitors for cancer immunotherapy. , However, unfavorable pharmacokinetics and possible neurotoxicity of Mn 2+ limited its wide applications in cancer immunotherapy . To improve the efficacy, various nanoparticle-based formulations have been developed to improve the immune activation effect of Mn 2+ . The formulation of Mn 2+ with antigens into a subunit cancer nanovaccine may be advantageous for spatiotemporal codelivery of the subunit antigens and Mn 2+ to the cytoplasm, where they may achieve orchestrated immune responses in the subcellular compartment.…”
mentioning
confidence: 99%
“…It has been widely reported that there is excessive GSH in the tumor microenvironment, which provides sufficient reductant for the reduction of MnO 2 ( 88 ). Under acidic conditions, GSH is oxidized to glutathione disulfide (GSSG) through mercaptan disulfide exchange, while MnO 2 is reduced to Mn 2+ ( 89 ). The reaction formula during the reaction between MnO 2 and GSH are as shown as following:…”
Section: The Significance Of Mno 2 For Cgas-sting ...mentioning
confidence: 99%
“…However, the poor stability of STING agonists and limited cell permeability have limited its promotion in the clinical setting. With the emergence of tumor immunotherapy, researchers have discovered that metal ions play an important role in immunomodulation and have proposed the concept of "metal immunotherapy" [ 240 , 241 ]. Moon et al [ 242 ] found that Mn 2+ could significantly enhance the activity of STING agonist IFN-I through screening and designed a self-assembled nanoparticle CMP (CDN-Mn 2+ particle) based on Mn 2+ and CDN STING agonist, and prepared CMP CDA by modification.…”
Section: Metallic Nanomaterialsmentioning
confidence: 99%